2011
DOI: 10.1371/journal.pone.0027856
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic Lipid Transfer Proteins from Plant-Derived Foods Do Not Immunologically and Clinically Behave Homogeneously: The Kiwifruit LTP as a Model

Abstract: BackgroundFood allergy is increasingly common worldwide. Tools for allergy diagnosis measuring IgE improved much since allergenic molecules and microarrays started to be used. IgE response toward allergens belonging to the same group of molecules has not been comprehensively explored using such approach yet.ObjectiveUsing the model of lipid transfer proteins (LTPs) from plants as allergens, including two new structures, we sought to define how heterogeneous is the behavior of homologous proteins.MethodsTwo new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 60 publications
(77 reference statements)
6
74
0
1
Order By: Relevance
“…Possible additional isoforms, suggested by elution profiles obtained during purification, were not identified probably because of the low yield. 72 MALDI-TOF mass spectrometry of purified nAct d 10 provided two mass values, 9.464 and 9.484 kDa, which are in good agreement with the values deduced from the amino acid sequence of the two isoforms having alanine (9.458 kDa) or threonine (9.488 kDa) as N-terminal residues, respectively. 72 Analysis by SDS-PAGE and RP-HPLC of LTP samples subjected to digestion in SGF showed that nAct c 10 and nAct d 10, similarly to nPru p 3, are resistant to gastric digestion.…”
Section: Act D 10supporting
confidence: 80%
See 2 more Smart Citations
“…Possible additional isoforms, suggested by elution profiles obtained during purification, were not identified probably because of the low yield. 72 MALDI-TOF mass spectrometry of purified nAct d 10 provided two mass values, 9.464 and 9.484 kDa, which are in good agreement with the values deduced from the amino acid sequence of the two isoforms having alanine (9.458 kDa) or threonine (9.488 kDa) as N-terminal residues, respectively. 72 Analysis by SDS-PAGE and RP-HPLC of LTP samples subjected to digestion in SGF showed that nAct c 10 and nAct d 10, similarly to nPru p 3, are resistant to gastric digestion.…”
Section: Act D 10supporting
confidence: 80%
“…72 Plant LTPs are widely distributed, structurally related, small proteins involved in defense mechanisms. Although their lipid binding ability has been well reported, the biological function of LTPs is still largely unknown.…”
Section: Act D 10mentioning
confidence: 99%
See 1 more Smart Citation
“…The kiwifruit is not a plant food that is commonly associated with LTP sensitization [8,14] in other series, although kiwifruit allergies with sensitization to its LTP Act d 10 have been reported in 22% of cases from Southern Europe [27]. Although the kiwifruit LTP seems to have slightly different properties than those of the classic LTPs [28], without overlooking the new and emerging kiwifruit allergens [29], we cannot dismiss the possibility that our patients reporting symptoms with kiwifruits could be sensitized to the LTP Act d 10. However, our data cannot draw any conclusions in this sense.…”
Section: Discussionmentioning
confidence: 99%
“…The described weaknesses of allergenomic strategies for new allergen identification lead to the necessity in the application of DNA-based techniques [115] or in Edman degradation performance for peptide sequencing [41,58,116,117,118]. It insures unequivocal identification of amino acid order in the peptide starting from the N-terminal residue and is typically realized in parallel with de novo sequencing [82][83][84].…”
Section: Allergenomics and New Allergen Discoverymentioning
confidence: 99%